Tourism for Sustainable Livelihood in Nepal (Voice of Teacher, 2021)
The main objective of the paper is to clarify the different adaptive strategies and livelihood pattern based on sports tourism initiatives in Nepali rural villages. The sustainable livelihood and adaptation of the natural resources especially in the rural areas of the country have been demanded to raise awareness and building capacity by attracting people from different countries through the organization of in-house and cross country tournaments and youth exchange programs. The livelihood is shaped as per the natural resources and other means provided in the area. This study has attempted to survey the climate change effects in the territory in long run. It has been possible by studying the changes and advancements experienced for twenty years back to today. While analyzing the different researches and studies of the past and the study has concluded that there are number of challenges despite of some progress and advancement in the livelihood. The majority of the population of Nepal resides in the rural areas so that the livelihood in general is critical in such areas. While studying for 20 years there have been changes and progresses in the livelihood pattern and adaptation strategies. The sports tourism has been found effective and efficient tool for the advocacy and lobbying in favor of livelihood promotion as well as sustainable development. The study and analysis of the documents have revealed that there has been tremendous efforts carried out in local level and more demand has been raised for national as well as international events. The sports tourism initiatives have been demanded for the accumulation of the climatic change effects as well as the environmental factors for poverty alleviation along with socio cultural prosperity.